Osteoinduction of human bone marrow cells: an in vitro study (Revista da Faculdade de Odontologia - UPF, 2012)
Objective: This study evaluated the osteogenic induction of human bone marrow cells by human recombinant bone morphogenetic protein-4 (rhBMP-4) and proteins released by Saos-2 (human osteosarcoma cell line). Study design: Osteoinduction in the presence or absence of Saos-2 and/or rhBMP-4 was evaluated in cultured human bone marrow cells. Morphological aspects and bone protein markers (osteonectin, osteopontin, and osteocalcin) were analyzed on days 1, 2, 5, 8, 11 and 14. Osteonectin expression was evaluated using immunohistochemistry with anti-secreted protein acidic and rich in cystein (anti-SPARC) antibody. mRNA transcripts for osteopontin were determined using RT-PCR with specific primers. Results: Bone marrow cells were adherent since the first day of culture and were positive for osteonectin. mRNA transcripts were detected in all culture conditions since the first day of culture. As human osteosarcoma cells are a source of additional growth they did not affect osteoinduction. rhBMP-4 up regulates osteoinduction during the first days of culture only. Osteoblasts were obtained from human bone marrow cells even in the absence of growth factors and showed a typical morphology. Cells derived from bone marrow can undergo osteoinduction in vitro in the absence of osteoinductive factors such as bone morphogenetic proteins. Conclusions: This study showed that an osteoblastic cell lineage may be obtained from human bone marrow derived from adherent cells, and that the presence of the rhBMP-4 seems to have an effect during the first stages of differentiation only.